Impact of doping and additive applications on photocatalyst textural properties in removing organic pollutants: A review - Safia Syazana, Mohtar; Farhana, Aziz; Ahmad Fauzi, Ismail; Nonni Soraya, Sambudi; Hamidah, Abdullah; Ahmad Nazrul, Rosli; Ohtani, Bunsho (MDPI, 2021)
The effect of ion doping and the incorporation of additives on photocatalysts’ textural properties have been reviewed. Generally, it can be summarised that ion doping and additives have beneficial effects on photocatalytic efficiency and not all have an increase in the surface area. The excessive amount of dopants and additives will produce larger aggregated particles and also cover the mesoporous structures, thereby increasing the pore size (Pd) and pore volume (Pv). An excessive amount of dopants also leads to visible light shielding effects, thus influence photocatalytic performance. Ion doping also shows some increment in the surface areas, but it has been identified that synergistic effects of the surface area, porosity, and dopant amount contribute to the photocatalytic performance. It is therefore important to understand the effect of doping and the application of additives on the textural properties of photocatalysts, thus, their performance. This review will provide an insight into the development of photocatalyst with better performance for wastewater treatment applications.